Development of a web-based online cooperative information system - Adamos, Edward A.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2009)
This study aims to design and develop a prototype of the Cooperative Information System. The system aims to provide a facility for cooperative members of the National Confederation of Cooperatives to submit periodic reports through a web-based information system. The system captures the information and is made available for retrieval and viewing.
The paper documents the software development cycle of the Cooperative information system. It illustrates the phases that the development went through. UML (Unified Modeling Language) Diagrams were used to represent the requirements of the federation. Screenshots of the system are also made available. Database diagrams and data dictionary tables are also provided. The system was made available for testing through a web host. It was then tested by determined users and an evaluation form was asked to be answered by the users. The result of the survey is also presented in the paper.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Information storage and retrieval systems